Historical cohort study of in utero exposure to uterotonic drugs and cognitive function in young adult life - Sørensen, Henrik Toft (1999)
•OBJECTIVE: To examine whether in utero exposure to uterotonic drugs effects cognitive performance in draft-age men. •DESIGN: Historical cohort study based on birth registry data and cognitive function measured during evaluations for military service. •SUBJECTS: 4300 Danish conscripts born between 1973 and 1975. •MAIN OUTCOME MEASURES: Mean score in the Boerge Prien test of cognitive function: score is the number of correct answers to 78 questions and correlates with the full scale intelligence quotient. •RESULTS: The mean Boerge Prien score was similar for those exposed (n=1011) to uterotonic drugs and those not exposed (n=3289), 43.1 versus 42.9 after adjustment for confounders. •CONCLUSION: Our data indicate that exposure to uterotonic drugs does not affect cognitive function 20 years later.